2019
DOI: 10.21273/hortsci14227-19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Arbuscular Mycorrhizal Inoculation and Growth Substrate on Biomass and Content of Polyphenols in Eclipta prostrata

Abstract: The aim of this study was to determine the influence of mycorrhizal inoculation and sand-peat composition as growth substrate on the biomass, and individual polyphenol concentration of Eclipta prostrata. Mycorrhizal inoculation alters some secondary metabolites of E. prostrata, showing significant differences in polyphenol contents between the treatments. Moreover, varying peat and sand rates, representing different nutrient supplies, had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…The difference in the second main constituent of polyphenols (4,5-dicaffeoylquinic acid in the present experiment versus demethyl wedelolactone in our previous one) may be attributable mainly to the different substrate volume we applied. The results demonstrated that under non-stress conditions, AM colonization considerably altered the content of six polyphenols in plants during growth stages, which is a confirmation with our previous findings showing that individual phenolics were influenced by AMF in this medicinal plant ( Vo et al, 2019 ). The reasons may be due to the mechanisms underlying AMF–plant interaction during mycorrhization.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The difference in the second main constituent of polyphenols (4,5-dicaffeoylquinic acid in the present experiment versus demethyl wedelolactone in our previous one) may be attributable mainly to the different substrate volume we applied. The results demonstrated that under non-stress conditions, AM colonization considerably altered the content of six polyphenols in plants during growth stages, which is a confirmation with our previous findings showing that individual phenolics were influenced by AMF in this medicinal plant ( Vo et al, 2019 ). The reasons may be due to the mechanisms underlying AMF–plant interaction during mycorrhization.…”
Section: Discussionsupporting
confidence: 90%
“…Noticeably, in the current work, we extended identifications to 14 individual phenolics. The findings showed that wedelolactone, an important phenolic compound to prevent inflammatory diseases and cancer in humans ( Sarveswaran et al, 2012 ), was one of the two main components of phenolic compounds in plants during growth stages under different conditions, which is in line with the earlier results ( Vo et al, 2019 ). The difference in the second main constituent of polyphenols (4,5-dicaffeoylquinic acid in the present experiment versus demethyl wedelolactone in our previous one) may be attributable mainly to the different substrate volume we applied.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations